Hot-pressed member, steel sheet for hot pressing, and method for manufacturing hot-pressed member
By setting the Al-Fe system intermetallic compound layer and the interface alloy layer on the hot pressing component, the Fe-rich structure is controlled, and the problem of large amount of hydrogen in the hot pressing component is solved, and the rapid release of hydrogen and the improvement of component strength is achieved. , reducing the risk of hydrogen embrittlement.
Patent Information
- Application Number
- CN202380043579.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-03-27
- Publication Date
- 2025-01-10
AI Technical Summary
The amount of hydrogen intrusion in the existing hot pressed parts during the manufacturing process is large and difficult to release in a short period of time, resulting in hydrogen embrittlement problems and affecting the strength and durability of the parts.
The hot pressed member is adopted which has an Al-Fe system intermetallic compound layer and a diffusion layer with a thickness of 10 to 35 μm. The layer contains more than 40% of the Al-rich phase and less than 40% of the Fe-rich phase, and the cross-sectional area ratio of the Fe-rich phase and the Fe-rich phase. The plating layer was formed by hot dip plating to control hydrogen release by combining an interface alloy layer with an Si concentration of 4%.
The amount of hydrogen invaded in the hot pressing process is significantly reduced, and hydrogen is released in a short time, which improves the delay fracture resistance and strength of the components, and reduces the risk of hydrogen embrittlement in the production process.
Smart Images

Figure BDA0005158484250000241 
Figure BDA0005158484250000251 
Figure BDA0005158484250000261
Abstract
Description
Technical Field
[0001] The present invention relates to a hot-pressed component, a steel plate for hot-pressing, and a method for manufacturing the hot-pressed component. Background Art
[0002] In recent years, in the automotive field, as the high performance of the blank steel sheet is improved, lightweighting is promoted, and the use of high-strength hot-dip galvanized steel sheets or electro-galvanized steel sheets with rust resistance is increasing. However, in most cases, as the steel sheet becomes stronger, its press formability decreases, so it is difficult to obtain a complex component shape. For example, in automotive applications, as parts that require rust resistance and are difficult to form, there can be cited running parts such as chassis, structural parts for skeletons such as B-pillars.
[0003] Based on this background, in recent years, the production of automotive parts by hot pressing, which is easier to achieve both press formability and high strength than cold pressing, has increased rapidly. Among them, Al-plated steel sheets have attracted much attention as steel sheets for hot pressing due to their excellent high-temperature oxidation resistance, and various Al-plated steel sheets suitable for hot pressing and hot-pressed parts using the Al-plated steel sheets have been proposed.
[0004] For example, Patent Document 1 proposes an Al-plated steel sheet for hot pressing, which has an Al-plated layer containing 1 to 15 mass % of Si and 0.5 to 10 mass % of Mg.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-034845 Summary of the invention
[0008] However, the conventional technology proposed in Patent Document 1 has the following problems.
[0009] That is, as mentioned above, hot pressing is widely used in the manufacture of structural parts for automotive frames, etc. Moreover, as hot pressed parts, parts with a tensile strength of 1.5 GPa after hot pressing are the mainstream, but in order to further reduce the weight of the automobile body, it is desired to have a high strength of 1.8 GPa or more.
[0010] However, as the strength of steel materials increases, the problem of hydrogen embrittlement becomes more prominent. Therefore, in order to increase the strength of hot-pressed parts, more advanced measures to combat hydrogen embrittlement are required.
[0011] Here, the causes of diffusible hydrogen intrusion into steel, which causes hydrogen embrittlement, can be roughly divided into two types: hydrogen intrusion during the manufacturing process of hot-pressed parts and hydrogen intrusion generated by corrosion reactions when hot-pressed parts are actually used. However, in the general use environment of automobiles, the corrosion rate of hot-pressed parts using Al-based plated steel sheets as blanks is low, and the amount of hydrogen generated by corrosion reactions is also small.
[0012] On the other hand, examples of hydrogen that intrudes during the manufacturing process of hot-pressed parts include hydrogen introduced during the manufacture of hot-pressed steel sheets, hydrogen introduced during the hot-pressing process, hydrogen introduced during the coating process, etc. It is known that in the case of hot-pressed parts using Al-plated steel sheets as blanks, the amount of hydrogen introduced during the hot-pressing process is very large.
[0013] Therefore, when using an Al-based plated steel sheet as a base material, it is particularly important to reduce the amount of diffusible hydrogen introduced during the hot pressing step.
[0014] On the other hand, even when a large amount of hydrogen is introduced into steel during the hot pressing process, the amount of hydrogen in the steel can sometimes be reduced by providing a sufficient residence time after hot pressing to release the hydrogen.
[0015] However, in hot-pressed parts using conventional Al-plated steel sheets as blanks, the release rate of hydrogen through the plating layer is very low. Therefore, in order to reduce the amount of diffusible hydrogen to a level that does not cause practical problems, it is necessary to significantly extend the residence time, which becomes a factor that reduces productivity.
[0016] Therefore, in addition to reducing the amount of hydrogen that penetrates during the hot pressing process, the hot pressed parts are also required to be able to release the penetrated hydrogen in a short time.
[0017] However, conventional hot-pressed parts cannot be said to have sufficient performance in terms of reducing the amount of intruded hydrogen and releasing the intruded hydrogen.
[0018] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a hot-pressed component having excellent delayed fracture resistance, in which a small amount of hydrogen intrudes during a hot-pressing process and the intruded hydrogen can be released in a short time.
[0019] An object of the present invention is to solve the above-mentioned problems, and the gist of the present invention is as follows.
[0020] 1. A hot pressing component, comprising:
[0021] Steel,
[0022] an Al-Fe-based intermetallic compound layer having a thickness of 10 to 35 μm and disposed on at least one surface of the steel material; and
[0023] a diffusion layer disposed at an interface between the Al-Fe-based intermetallic compound layer and the steel material;
[0024] The Al—Fe-based intermetallic compound layer includes an Al-rich phase having an Al concentration of 40 mass % or more and an Fe-rich phase having an Al concentration of less than 40 mass %.
[0025] The average length of the cross section of the Fe-rich phase in a direction perpendicular to the plate thickness direction is 10 μm or less.
[0026] 2. The hot-pressed component according to item 1 above, wherein the amount of diffusible hydrogen in the steel material is 0.30 mass ppm or less.
[0027] 3. A hot pressing steel plate, comprising:
[0028] Base steel plate, and
[0029] A plating layer having a thickness of 10 to 35 μm disposed on at least one surface of the base steel plate;
[0030] The above-mentioned coating has:
[0031] An interface alloy layer disposed on the above-mentioned base steel plate, and
[0032] A metal layer having an Al content of 50 mass % or more disposed on the interface alloy layer;
[0033] The interface alloy layer includes a Si-rich phase having a Si concentration of 4 mass % or more,
[0034] The cross-sectional area ratio of the Si-rich phase to the entire interface alloy layer is 5% to 30%.
[0035] 4. The hot-pressing steel sheet according to item 3 above, wherein the metal layer contains:
[0036] Si: 0.5 to 7.0 mass %, and
[0037] Fe: 0 to 30 mass %.
[0038] 5. The hot-pressing steel sheet according to 4 above, wherein the metal layer further contains:
[0039] Mg: 0.1 to 4.0 mass %.
[0040] 6. A method for producing a hot pressed component, comprising hot pressing the steel sheet for hot pressing according to any one of 3 to 5 above to produce a hot pressed component.
[0041] According to the present invention, a hot pressed component can be obtained which has a small amount of hydrogen intruded during a hot pressing process, can release the intruded hydrogen in a short time, and has excellent delayed fracture resistance. DETAILED DESCRIPTION
[0042] Hereinafter, an embodiment of the present invention will be described. It should be noted that the following description shows a preferred embodiment of the present invention and is not limited in any way to the following description. In addition, "%" as a unit of content means "mass %" unless otherwise specified.
[0043] (1) Hot pressing parts
[0044] A hot-pressed component according to one embodiment of the present invention includes a steel material as a base material, an Al-Fe-based intermetallic compound layer disposed on at least one surface of the steel material, and a diffusion layer formed at an interface between the Al-Fe-based intermetallic compound layer and the steel material. Each part will be described below.
[0045] [Steel]
[0046] In the present invention, the above-mentioned problems are solved by providing an Al—Fe-based intermetallic compound layer and a diffusion layer satisfying predetermined conditions on the surface of a steel material as described below. Therefore, any steel material can be used as the above-mentioned steel material without any particular limitation.
[0047] It should be noted that the hot-pressed component of the present invention is manufactured by hot-pressing a hot-pressing steel plate as described below. Therefore, the above-mentioned steel material can also be said to be a steel plate formed by hot pressing. As the above-mentioned steel plate, any one of a cold-rolled steel plate and a hot-rolled steel plate can be used.
[0048] The hot pressed part preferably has high strength from the viewpoint of use as an automobile part, etc. In particular, in order to obtain a hot pressed part having a tensile strength exceeding 980 MPa, preferably 1.8 GPa or more, it is preferable to use a steel material having the following component composition.
[0049] The composition contains:
[0050] C: 0.05~0.50%,
[0051] Si: 0.1-1.5%,
[0052] Mn: 0.5-5.0%,
[0053] P: 0.1% or less,
[0054] S: 0.01% or less,
[0055] Al: 0.10% or less, and
[0056] N: 0.01% or less,
[0057] The remainder consists of Fe and inevitable impurities.
[0058] Hereinafter, the effects and preferred contents of the respective elements in the above-mentioned preferred component composition will be described.
[0059] C: 0.05~0.50%
[0060] C is an element that has the effect of increasing strength by forming a structure such as martensite. From the viewpoint of obtaining a strength exceeding 980MPa level, it is preferred that the C content be 0.05% or more, more preferably 0.10% or more. On the other hand, if the C content exceeds 0.50%, the toughness of the spot weld deteriorates. Therefore, the C content is preferably 0.50% or less, more preferably 0.45% or less, further preferably 0.43% or less, and most preferably 0.40% or less.
[0061] Si: 0.1-1.5%
[0062] Si is an effective element for strengthening steel and obtaining good material quality. In order to obtain the above-mentioned effect, it is preferred that the Si content is 0.1% or more, and more preferably 0.2% or more. On the other hand, if the Si content exceeds 1.5%, ferrite is stabilized, so hardenability decreases. Therefore, the Si content is preferably 1.5% or less, more preferably 1.3% or less, and further preferably 1.1% or less.
[0063] Mn: 0.5~5.0%
[0064] Mn is an effective element for obtaining high strength regardless of the cooling rate. From the viewpoint of ensuring excellent mechanical properties and strength, the Mn content is preferably 0.5% or more, more preferably 0.7% or more, and further preferably 1.0% or more. On the other hand, if the Mn content exceeds 5.0%, not only the cost increases, but also the effect of adding Mn is saturated. Therefore, the Mn content is preferably 5.0% or less, more preferably 4.5% or less, and further preferably 4.0% or less.
[0065] P: 0.1% or less
[0066] If the P content is excessive, the local ductility deteriorates due to grain boundary embrittlement accompanied by P segregation to the austenite grain boundary during casting. And, as a result, the balance between the strength and ductility of the steel plate is reduced. Therefore, from the viewpoint of improving the balance between the strength and ductility of the steel plate, it is preferred that the P content is 0.1% or less. On the other hand, from the viewpoint of refining cost, it is preferred that the P content is 0.01% or more.
[0067] S: 0.01% or less
[0068] S becomes inclusions such as MnS, which causes deterioration of impact resistance and cracks due to metal flow along the weld. Therefore, it is desirable to reduce the S content as much as possible, and specifically, it is preferably 0.01% or less. In addition, from the viewpoint of ensuring good stretch flangeability, it is more preferably 0.005% or less, and further preferably 0.001% or less. On the other hand, from the viewpoint of refining cost, it is preferable to make the S content 0.0002% or more.
[0069] Al: 0.10% or less
[0070] Al is an element that functions as a deoxidizer. However, if the Al content exceeds 0.1%, the blanking workability and hardenability of the steel plate will decrease. Therefore, the Al content is preferably 0.10% or less, more preferably 0.07% or less, and further preferably 0.04% or less. On the other hand, from the viewpoint of ensuring the effect as a deoxidizer, the Al content is preferably 0.01% or more.
[0071] N: 0.01% or less
[0072] If the N content exceeds 0.01%, AlN nitrides are formed during hot rolling and heating before hot pressing, which reduces the blanking workability and hardenability of the steel sheet. Therefore, the N content is preferably 0.01% or less. On the other hand, from the perspective of refining cost, the N content is preferably 0.001% or more.
[0073] In addition, the above composition may further contain any of the following:
[0074] Nb: 0.10% or less,
[0075] Ti: 0.05% or less,
[0076] B: 0.0002~0.005%,
[0077] Cr: 0.1-1.0%, and
[0078] Sb: 0.003~0.03%
[0079] At least one of .
[0080] Nb: 0.10% or less
[0081] Nb is an effective component for strengthening steel, but if it is contained in excessive amount, the rolling load increases. Therefore, when Nb is added, it is preferable to make the Nb content 0.10% or less, and more preferably 0.05% or less. On the other hand, the lower limit of the Nb content is not particularly limited, and may be 0%, but from the viewpoint of refining cost, the Nb content may be 0.005% or more.
[0082] Ti: 0.05% or less
[0083] Ti is a component effective for strengthening steel like Nb, but if it is contained in excessive amount, the shape fixity will be reduced. Therefore, when Ti is added, it is preferable to make the Ti content 0.05% or less, and more preferably 0.03% or less. On the other hand, the lower limit of the Ti content is not particularly limited and may be 0%, but from the viewpoint of refining cost, it is preferable to make the Ti content 0.005% or more.
[0084] B: 0.0002~0.005%
[0085] B has the effect of inhibiting the formation and growth of ferrite from austenite grain boundaries. When B is added, in order to obtain the above effect, the B content is preferably 0.0002% or more, and more preferably 0.0010% or more. On the other hand, adding excessive B will reduce formability. Therefore, when B is added, the B content is preferably 0.005% or less, and more preferably 0.003% or less.
[0086] Cr: 0.1~1.0%
[0087] Cr is an element useful for improving the strengthening and hardenability of steel, just like Mn. When adding Cr, in order to obtain the above-mentioned effect, the Cr content is preferably 0.1% or more, more preferably 0.2% or more. On the other hand, since Cr is an expensive element, adding excessive Cr will lead to a significant increase in cost. Therefore, when adding Cr, the Cr content is preferably 1.0% or less, more preferably 0.6% or less.
[0088] Sb: 0.003~0.03%
[0089] Sb is an element that has the effect of suppressing decarburization of the surface layer of the steel plate in the annealing process when manufacturing the base steel plate. In the case of adding Sb, in order to obtain the above-mentioned effect, the Sb content is preferably 0.003% or more, and more preferably 0.005% or more. On the other hand, if the Sb content exceeds 0.03%, the rolling load increases, so the productivity decreases. Therefore, in the case of adding Sb, the Sb content is preferably 0.03% or less, more preferably 0.02% or less, and further preferably 0.01% or less.
[0090] [Al-Fe based intermetallic compound layer]
[0091] The hot-pressed component of the present invention has an Al-Fe intermetallic compound layer on at least one surface of the steel material. By providing a layer composed of an Al-Fe intermetallic compound on the surface of the hot-pressed component, the generation and intrusion of hydrogen accompanying the corrosion of the steel material can be prevented. For example, even in the case where a coating is provided on the surface of the hot-pressed component, corrosion usually proceeds from the scars of the coating, the ends of the coating, and other locations where the rust-proof function of the coating is reduced. However, by the presence of the Al-Fe intermetallic compound, corrosion can be suppressed even in this case, and as a result, the generation and intrusion of hydrogen can be prevented.
[0092] The Al—Fe-based intermetallic compound layer may be provided on at least one surface of the steel material, but is preferably provided on both surfaces.
[0093] The type of the intermetallic compound constituting the Al-Fe based intermetallic compound layer is not particularly limited. Examples of the constituent elements of the Al-rich phase include FeAl3, Fe4Al 13 , Fe2Al5, etc. As constituent elements of the Fe-rich phase, FeAl, Fe3Al, etc. are exemplified. In addition, the Al-Fe intermetallic compound may also contain Al-Fe-Si intermetallic compounds such as Fe2Al5Si. That is, the Al-Fe intermetallic compound layer in one embodiment of the present invention may contain FeAl3, Fe4Al 13 , Fe2Al5, FeAl, Fe3Al and Fe2Al5Si. In addition, the Al-Fe intermetallic compound layer may also be a layer selected from FeAl3, Fe4Al 13 The layer may be composed of at least one of Fe2Al5, FeAl, Fe3Al and Fe2Al5Si. The types of these intermetallic compounds can be identified by X-ray diffraction.
[0094] Average length: less than 10μm
[0095] In the hot-pressed part of the present invention, the Al-Fe intermetallic compound layer includes an Al-rich phase having an Al concentration of 40% or more and an Fe-rich phase having an Al concentration of less than 40%. Moreover, in the present invention, it is important to make the average length of the cross section of the Fe-rich phase in the direction perpendicular to the plate thickness direction be less than 10 μm. The reasons for this are explained below.
[0096] Generally, when hot pressing is performed on an Al-plated steel sheet, an Al-Fe-based intermetallic compound layer is formed, but the Al-Fe-based intermetallic compound layer has a layered structure. Typically, the Al-Fe-based intermetallic compound layer has a structure in which three or more layers, more usually five or more layers, of Al-rich phases and Fe-rich phases are alternately stacked.
[0097] The results of the research conducted by the present inventors show that when the Al-Fe intermetallic compound layer has the above-mentioned layer structure, hydrogen is trapped at the interface between the layers, so the release of hydrogen is hindered. That is, in the conventional hot-pressed parts, due to the structure of the Al-Fe intermetallic compound layer, the release rate of hydrogen that penetrates into the steel during the hot-pressing process becomes extremely slow.
[0098] In contrast, in the hot-pressed part of the present invention, the average length of the cross section of the Fe-rich phase in the direction perpendicular to the plate thickness direction (hereinafter sometimes referred to as "average length") is less than 10 μm. This means that the Fe-rich phase is finely divided in the plate surface direction. The hot-pressed part of the present invention has excellent hydrogen release characteristics because it has a structure in which the Fe-rich phase is divided. In this way, the present invention is based on a completely new technical concept of promoting the release of hydrogen by dividing the Fe-rich phase.
[0099] From the viewpoint of hydrogen release characteristics, the average length is preferably 8 μm or less, more preferably 6 μm or less. On the other hand, the lower limit of the average length is not particularly limited, but from the viewpoint of scratch resistance, the average length is preferably 2 μm or more, preferably 3 μm or more.
[0100] In addition, the cross-sectional area ratio of the Fe-rich phase in the Al-Fe intermetallic compound layer is not particularly limited, but is preferably 30% or less, more preferably 20% or less, and further preferably 10% or less from the viewpoint of further improving the hydrogen release rate. On the other hand, the lower limit of the cross-sectional area ratio of the Fe-rich phase is not particularly limited, but Al is softer than Fe, so if there is no Fe-rich phase and it is a single Al-rich phase, the scratch resistance is reduced. Therefore, from the viewpoint of scratch resistance, the cross-sectional area ratio of the Fe-rich phase is preferably 3% or more, and more preferably 5% or more.
[0101] In addition, from the viewpoint of further increasing the hydrogen release rate, it is preferred that the Fe-rich phase be distributed in the Al-rich phase in an island shape.
[0102] The structure of the Al-Fe intermetallic compound layer, the size of each phase, and the cross-sectional area ratio can be measured by observing the cross section of the Al-Fe intermetallic compound layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX) and analyzing the obtained image. More specifically, the measurement can be performed by the method described in the Examples.
[0103] Thickness: 10~35μm
[0104] The thickness of the Al-Fe intermetallic compound layer depends on the plating thickness of the hot-pressing steel sheet used and the hot-pressing conditions. If the thickness of the Al-Fe intermetallic compound layer is less than 10 μm, the desired corrosion resistance after coating cannot be obtained. Therefore, the thickness of the Al-Fe intermetallic compound layer is greater than 10 μm, preferably greater than 13 μm, and more preferably greater than 15 μm. On the other hand, if the thickness of the Al-Fe intermetallic compound layer exceeds 35 μm, even if the morphology of the Fe-rich phase meets the requirements of the present invention, the time required for dehydrogenation becomes longer. Therefore, the thickness of the Al-Fe intermetallic compound layer is less than 35 μm, preferably less than 30 μm, and more preferably less than 25 μm.
[0105] The thickness of the Al-Fe intermetallic compound layer can be measured by the method described in the examples. It should be noted that when the Al-Fe intermetallic compound layer is provided on both sides of the steel material, the thickness of the Al-Fe intermetallic compound layer on each side is 10 to 35 μm. However, the thickness of the Al-Fe intermetallic compound layer on one side may be the same as or different from the thickness of the Al-Fe intermetallic compound layer on the other side.
[0106] [Diffusion layer]
[0107] The hot-pressed component of the present invention has a diffusion layer formed at the interface between the Al-Fe intermetallic compound layer and the steel material. The diffusion layer has a larger hydrogen diffusion coefficient than the intermetallic compound layer, so it does not hinder the release of hydrogen. Therefore, in the present invention, the thickness of the diffusion layer is not limited, but in order to maintain good adhesion between the Al-Fe intermetallic compound layer and the steel material, it is preferably 1 μm or more. In addition, for the same reason, the thickness of the diffusion layer is preferably 20 μm or less.
[0108] The amount of diffusible hydrogen in the steel of the hot-pressed component of the present invention is not particularly limited, and is preferably 0.30 mass ppm or less. If the amount of diffusible hydrogen is 0.30 mass ppm or less, the risk of delayed fracture when residual stress is generated due to assembly and welding of the hot-pressed component can be further reduced. In order to further reduce the risk of delayed fracture, it is more preferred to make the amount of diffusible hydrogen in the steel be 0.20 mass ppm or less, and more preferably 0.10 mass ppm or less. The lower the amount of diffusible hydrogen, the better, so the lower limit is not particularly limited, and can be 0 mass ppm, but considering the quantitative limit of the analysis, it can be 0.01 mass ppm or more.
[0109] In the present invention, the cumulative value of the amount of hydrogen when the temperature is raised to 300° C. by temperature desorption analysis after the Al—Fe-based intermetallic compound layer is removed by polishing or the like is defined as the diffusible hydrogen amount.
[0110] The strength of the hot pressed part is not particularly limited, but the hot pressed part is generally used in applications requiring strength such as automotive parts, so high strength is desired. In particular, a tensile strength of more than 1320 MPa is required for skeleton parts such as center columns that suppress deformation due to collisions. Therefore, the tensile strength of the hot pressed part is preferably more than 1320 MPa, more preferably more than 1.5 GPa, and further preferably more than 1.8 GPa. On the other hand, the upper limit of the tensile strength is not particularly limited, but typically it can be less than 2.5 GPa, and can also be less than 2.2 GPa.
[0111] In addition, when used in components such as side beams that require energy absorption, excellent yield strength and elongation are required. Therefore, the yield strength of the hot-pressed component is preferably greater than 700 MPa. In addition, the total elongation of the hot-pressed component is preferably greater than 7%. On the other hand, the upper limit of the yield strength is not particularly limited, but typically it can be less than 1100 MPa, and can also be less than 900 MPa. In addition, the upper limit of the total elongation is not particularly limited, but typically it can be less than 20%, and can also be less than 15%.
[0112] (2) Steel plates for hot pressing
[0113] A hot pressing steel sheet in one embodiment of the present invention comprises a base steel sheet and a coating layer having a thickness of 10 to 35 μm disposed on at least one surface of the steel sheet. Furthermore, the coating layer comprises an interface alloy layer disposed on the base steel sheet and a metal layer having an Al content of 50% or more disposed on the interface alloy layer. The interface alloy layer comprises a Si-rich phase having a Si concentration of 4% or more, and the cross-sectional area ratio of the Si-rich phase relative to the entire interface alloy layer is 5% to 30%.
[0114] [Plating]
[0115] If the thickness of the above-mentioned coating is less than 10μm, in addition to not being able to obtain sufficient corrosion resistance, the amount of hydrogen intrusion caused by corrosion increases, and the delayed fracture resistance decreases. Therefore, the thickness of the coating is set to be 10μm or more, preferably 12μm or more, and more preferably 15μm or more. On the other hand, if the thickness of the coating exceeds 35μm, the oxidation amount of the coating becomes large, so the amount of diffusible hydrogen cannot be fully reduced. Therefore, the thickness of the coating is 35μm or less, preferably 30μm or less, and more preferably 25μm or less. It should be noted that when there is a coating on both sides of the base steel plate, the thickness of the coating is set to 10μm to 35μm on either side. The thickness of the above-mentioned coating can be directly measured by using an electromagnetic film thickness gauge.
[0116] The thickness of the plating layer on one surface of the base steel plate may be the same as or different from the thickness of the plating layer on the other surface. In other words, the thickness of the plating layer on one surface of the base steel plate may be 10 μm to 35 μm, and the thickness of the plating layer on the other surface may also be 10 μm to 35 μm.
[0117] The above-mentioned coating layer can be directly provided on the surface of the base steel plate, but another layer (base coating) can be further provided between the base steel plate and the coating layer. The above-mentioned lower coating layer can be, for example, a second coating layer (base coating layer) having a composition different from that of the above-mentioned coating layer. As the above-mentioned second coating layer, for example, a base coating layer mainly composed of Fe or Ni is preferably used.
[0118] In addition, the hot-pressing steel sheet of the present invention may further include another layer (upper film) on the above-mentioned coating. As the above-mentioned upper film, for example, a third coating having a composition different from that of the above-mentioned coating or a chemical conversion coating may be used. As the above-mentioned third coating, for example, a post-plating layer mainly composed of Ni is preferably used. In addition, as the above-mentioned chemical conversion coating, for example, a chemical conversion coating containing phosphate, zirconium compound, titanium compound, etc. is preferably used.
[0119] [Interface alloy layer]
[0120] The hot-pressing steel sheet is typically produced by hot-dip plating a base steel sheet as follows: Fe, Mn, etc. contained in the base steel sheet react with Al, Si, etc. contained in the plating bath to form an interface alloy layer at the interface between the base steel sheet and the metal layer.
[0121] Cross-sectional area ratio of Si-rich phase: 5% to 30%
[0122] In the hot-pressing steel sheet of the present invention, it is important that the interface alloy layer includes a Si-rich phase having a Si concentration of 4% or more, and the cross-sectional area ratio of the Si-rich phase to the entire interface alloy layer is 5% to 30%. The reasons for this are described below.
[0123] As described above, in the hot-pressed part of the present invention, excellent hydrogen release characteristics are achieved by finely dividing the Fe-rich phase included in the Al—Fe-based intermetallic compound layer in the sheet surface direction.
[0124] Furthermore, the inventors have studied and found that the structure of the Fe-rich phase in the Al—Fe intermetallic compound layer of the hot-pressed component depends on the proportion of the Si-rich phase in the interface alloy layer of the hot-pressed steel sheet.
[0125] The detailed mechanism is not clear, but it is speculated that the Si-rich phase has a higher melting point than the phase with a low Si concentration and does not melt during hot pressing. By controlling the proportion of the Si-rich phase in the interface alloy layer within an appropriate range and reducing the cross-sectional area ratio and length of the Fe-rich phase in the Al-Fe intermetallic compound layer of the hot-pressed part, a hot-pressed part with a high hydrogen desorption rate can be obtained.
[0126] If the cross-sectional area ratio of the Si-rich phase relative to the entire interface alloy layer is higher than 30%, the Fe-rich phase in the Al-Fe intermetallic compound layer of the hot-pressed component becomes continuous, and the desired hydrogen desorption characteristics cannot be obtained. Therefore, the cross-sectional area ratio of the Si-rich phase is less than 30%. On the other hand, the Si-rich phase also has the effect of reducing the diffusion of Fe from the base steel plate to the coating during the hot pressing process and inhibiting the excessive thickening of the Al-Fe intermetallic compound layer in the hot-pressed component. As mentioned above, if the Al-Fe intermetallic compound layer is too thick, the hydrogen desorption rate decreases. Therefore, the cross-sectional area ratio of the above-mentioned Si-rich phase is greater than 5%. If the cross-sectional area ratio of the above-mentioned Si-rich phase is greater than 5%, it is easy to make the thickness of the Al-Fe intermetallic compound layer within the desired range. As a result, the manufacturing conditions (heating conditions, etc.) used to obtain the hot-pressed component are relaxed, and the productivity is improved.
[0127] It should be noted that the Si-rich phase herein refers to a phase having a Si concentration of 4% or more.
[0128] The upper limit of the Si concentration in the Si-rich phase is not particularly limited, but is preferably 30% or less. In addition, there is no particular limitation on the components other than Si in the Si-rich phase, but in one embodiment of the present invention, the Si-rich layer may contain any components from the base steel plate and the plating layer in addition to Si. The Si-rich phase preferably contains Fe, Mn and Al in addition to Si. As a typical composition of the Si-rich phase, it is exemplified that it contains Fe: 20-40%, Si: 4-30% and Mn: 0.1-5%, and the remainder is composed of Al and unavoidable impurities.
[0129] In the present invention, the structure of the Al-Fe intermetallic compound layer in the hot-pressing steel sheet is controlled by controlling the cross-sectional area ratio of the Si-rich phase in the interface alloy layer. Therefore, the distribution and shape of the Si-rich phase in the interface alloy layer are not particularly limited. The Si-rich phase may be, for example, layered.
[0130] The phase separation in the interface alloy layer can be determined by analyzing an image obtained by SEM observation with EDX, or more specifically, by the method described in the Examples.
[0131] [Metal layer]
[0132] The hot-pressing steel sheet of the present invention has a metal layer on the interface alloy layer. The metal layer may have an Al content of 50% or more, and other compositions are not particularly limited.
[0133] In one embodiment of the present invention, the metal layer may contain Si: 0.5 to 7.0% and Fe: 0 to 30%. The reason for this will be described below.
[0134] Si: 0.5-7.0%
[0135] The Si in the metal layer alloys with Al and Fe during the hot pressing process to form Al-Fe-Si intermetallic compounds, especially the above-mentioned Fe-rich phase. In order to make the Fe-rich phase in the Al-Fe intermetallic compound layer of the hot-pressed component discontinuous, it is important to limit the amount of Si in the metal layer, so the Si concentration in the metal layer is preferably 7.0% or less. The Si concentration in the metal layer is more preferably 5.0% or less, and further preferably 3.0% or less. On the other hand, if the Si concentration is less than 0.5%, it is difficult to form the Fe-rich phase in the Al-Fe intermetallic compound layer of the hot-pressed component, resulting in reduced scratch resistance. Therefore, the Si concentration in the metal layer is preferably 0.5% or more, and more preferably 1.0% or more.
[0136] Fe: 0-30%
[0137] When the plating layer is formed by hot-dip plating, Fe is contained in the metal layer by forming an alloy layer through the reaction between the plating bath and the base material, and is contained in the metal layer by dissolving the base material into the plating bath and hot-dip plating. The Fe concentration in the metal layer is mainly determined by the thickness of the alloy layer formed by the reaction between the plating bath and the base material, and therefore varies with the plating bath temperature, the temperature and surface state of the plate when immersed in the plating bath, the residence time of the plate in the bath, etc.
[0138] If the Fe concentration in the metal layer exceeds 30%, the intermetallic compound containing Fe in the metal layer precipitates excessively. As a result, the alloying speed becomes faster and the intermetallic compound layer in the hot-pressed part tends to become thicker. Therefore, the Fe concentration in the metal layer is preferably 30% or less, more preferably 18% or less, and further preferably 12% or less. On the other hand, from the viewpoint of reducing the intermetallic compounds in the hot-pressed steel sheet, the Fe concentration in the metal layer is preferably lower. Therefore, the lower limit of the Fe concentration in the metal layer is 0%.
[0139] In the steel sheet for hot pressing according to one embodiment of the present invention, the metal layer preferably has a component composition containing Si: 0.5 to 7.0% and Fe: 0 to 30%, with the remainder being Al and inevitable impurities.
[0140] As the above-mentioned inevitable impurities, components from the base steel plate and inevitable impurities in the plating bath can be cited. The total content of the above-mentioned inevitable impurities is not particularly limited. However, from the viewpoint of preventing the precipitation of intermetallic compounds having a potential difference with the metal layer and deteriorating the corrosion resistance of the plating layer, the total amount of inevitable impurities contained in the plating layer is preferably 1% or less.
[0141] The metal layer preferably further contains Mg: 0.1 to 4.0%. The reason for this will be described below.
[0142] Mg: 0.1~4.0%
[0143] Diffusible hydrogen in hot-pressed parts is generated when the metal of the plated layer is oxidized by water vapor contained in the atmosphere during the hot-pressing process. For example, in the surface layer of a general hot-pressed Al-plated steel sheet, there are metallic Al and Si, which react with water vapor to generate hydrogen atoms. At this time, the atomic valence of Al is 3, so 3 hydrogen atoms are generated when Al reacts with water vapor. Similarly, since the atomic valence of Si is 4, 4 hydrogen atoms are generated when Si reacts with water vapor.
[0144] In contrast, since the atomic valence of Mg is 2, the amount of hydrogen generated per atom is less than that of Al and Si. In addition, Mg is more oxidizable than Al and Si, so in the presence of Mg, water vapor reacts with Mg preferentially. Therefore, by including Mg in the plating layer, the amount of hydrogen generated can be reduced.
[0145] If the Mg concentration in the metal layer is 0.1% or more, the oxidation of Al is fully suppressed, so the amount of diffusible hydrogen is further reduced. Therefore, from the viewpoint of further reducing the amount of diffusible hydrogen, it is preferred that the Mg concentration in the metal layer be 0.1% or more, more preferably 0.3% or more, and even more preferably 1% or more. On the other hand, if the Mg concentration is 4.0% or less, the oxide formed by the oxidation of Mg is not granular but film-like, and the protection against the oxidation of Mg itself is improved. And as a result, the amount of diffusible hydrogen is further reduced. Therefore, from the viewpoint of further reducing the amount of diffusible hydrogen, it is preferred that the Mg concentration be 4.0% or less, more preferably 3.0% or less, and even more preferably 2.0% or less.
[0146] In other embodiments of the present invention, the component composition of the above-mentioned metal layer may further contain at least one selected from Mn, V, Cr, Mo, Ti, Ni, Co, Sb, Zr and B in a total amount of less than 1%.
[0147] (3) Method for manufacturing hot-pressed parts
[0148] Next, a preferred method for producing the hot-pressed component of the present invention will be described.
[0149] In one embodiment of the present invention, the hot-pressed component is manufactured by hot-pressing the plated steel sheet for hot-pressing. The hot-pressed component satisfying the above conditions can be obtained by hot-pressing the steel sheet for hot-pressing satisfying the above conditions under general conditions.
[0150] The method for hot pressing is not particularly limited and can be carried out according to conventional methods. Typically, the hot pressing steel sheet is heated to a predetermined heating temperature (heating process), and then the hot pressing steel sheet heated in the heating process is hot pressed (hot pressing process). The preferred hot pressing conditions are described below.
[0151] [heating]
[0152] If the heating temperature in the above-mentioned heating process is lower than the Ac3 transformation point of the base steel plate, the strength of the final hot-pressed component becomes lower. Therefore, the above-mentioned heating temperature is preferably above the Ac3 transformation point of the base steel plate. The above-mentioned heating temperature is preferably above 860°C. On the other hand, if the above-mentioned heating temperature exceeds 1000°C, the oxide layer produced by oxidation of the base material and the coating layer becomes too thick, which may deteriorate the paint adhesion of the obtained hot-pressed component. Therefore, the above-mentioned heating temperature is preferably below 1000°C, more preferably below 960°C, and further preferably below 920°C. It should be noted that the Ac3 transformation point of the base steel plate varies depending on the steel composition, but is obtained by a fully automatic phase transformation (Formaster) test.
[0153] The temperature at which the heating is started is not particularly limited, but is generally room temperature.
[0154] The time (heating time) required for heating from the start of heating to the temperature rise reaching the above-mentioned heating temperature is not particularly limited and can be any time. However, if the above-mentioned heating time exceeds 300 seconds, the time of exposure to high temperature becomes long, so the oxide layer produced by oxidation of the base material and the coating becomes too thick. Therefore, from the viewpoint of suppressing the reduction of the coating adhesion caused by the oxide, it is preferred that the above-mentioned heating time is less than 300 seconds, more preferably less than 270 seconds, and more preferably less than 240 seconds. On the other hand, if the above-mentioned heating time is less than 150 seconds, there is a risk of excessive melting of the coating layer during heating, contaminating the heating device and the mold. Therefore, from the viewpoint of further improving the effect of preventing the pollution of the heating device and the mold, it is preferred that the above-mentioned heating time is more than 150 seconds, more preferably more than 180 seconds, and more preferably more than 210 seconds.
[0155] After reaching the above-mentioned heating temperature, it can be maintained at the heating temperature. In the case of the above-mentioned maintenance, the holding time is not particularly limited, and any length of maintenance can be performed. However, if the holding time exceeds 300 seconds, the oxide layer produced by oxidation of the base material and the coating layer becomes too thick, which may deteriorate the coating adhesion of the obtained hot-pressed parts. Therefore, the holding time is preferably less than 300 seconds, more preferably less than 210 seconds, and further preferably less than 120 seconds. On the other hand, the lower limit of the holding time is also not limited, and it can be 0 seconds, but from the viewpoint of uniformly austenitizing the base material steel plate, it is preferably more than 10 seconds.
[0156] The atmosphere in the heating step is not particularly limited, and the heating can be performed in an air atmosphere or in an atmosphere in which the air atmosphere circulates. From the viewpoint of further reducing the amount of diffusible hydrogen remaining in the hot-pressed component, the dew point of the atmosphere is preferably set to 0°C or less. The lower limit of the dew point is also not particularly limited, and can be, for example, -40°C or more.
[0157] The method for heating the hot-pressing steel sheet is not particularly limited, and the steel sheet may be heated by any method. The heating may be performed, for example, by heating using a furnace, electric heating, induction heating, high-frequency heating, flame heating, etc. As the heating furnace, any heating furnace such as an electric furnace and a gas furnace may be used.
[0158] [Heat Pressing]
[0159] After the above heating, the steel plate is hot pressed to form a hot pressed part. In the above hot pressing, cooling is performed using a cooling medium such as a mold or water while or immediately after the processing. In the present invention, the hot pressing conditions are not particularly limited. For example, pressing can be performed at a general hot pressing temperature range, i.e., 600 to 800°C.
[0160] (4) Method for manufacturing steel sheet for hot pressing
[0161] Next, a preferred method for producing the hot pressing steel sheet of the present invention will be described.
[0162] The hot press steel sheet of the present invention can be produced by hot dipping a base steel sheet. However, in order to make the cross-sectional area ratio of the Si-rich phase in the obtained hot press steel sheet 30% or less, both the following (A) and (B) need to be performed during the production process.
[0163] (A) Reduce the amount of Si in the plating bath
[0164] (B) Reducing the amount of Si in the outermost layer of the steel plate
[0165] Furthermore, specific examples of the method for (B) include the following (B-1) to (B-3).
[0166] (B-1) Increase in coiling temperature after hot rolling
[0167] (B-2) Recrystallization annealing to increase the dew point
[0168] (B-3) Formation of Fe-based pre-plating layer
[0169] Hereinafter, specific conditions for producing a hot-pressing steel sheet by these methods will be described.
[0170] [Base Steel Plate]
[0171] As the base steel plate, any steel plate can be used without particular limitation. The component composition of the base steel plate is not particularly limited, but is preferably the same as the preferred component composition of the steel material.
[0172] The above-mentioned base steel plate may be any one of a hot-rolled steel plate and a cold-rolled steel plate.
[0173] When a hot rolled steel sheet is used as the base steel sheet, the hot rolled steel sheet can be manufactured according to a conventional method. Typically, a steel sheet as a blank is heated and then hot rolled. In the hot rolling, rough rolling and finish rolling can be performed in sequence. Preferably, pickling is performed after the hot rolling.
[0174] (B-1) Increase in coiling temperature after hot rolling
[0175] The obtained hot-rolled steel sheet is coiled into a coil. At this time, by increasing the coiling temperature, an internal oxide can be formed inside the surface layer of the steel sheet. By forming an internal oxide, the diffusion rate of Si to the outermost layer of the steel sheet during hot dip plating can be reduced, and as a result, the cross-sectional area ratio of the Si-rich phase in the hot-pressed steel sheet can be reduced. Therefore, in order to make the cross-sectional area ratio of the Si-rich phase less than 30%, the coiling temperature is set to 600°C or more, preferably 620°C or more, more preferably 630°C or more, and further preferably 650°C or more. On the other hand, if the coiling temperature is too high, the internal oxide layer of the steel sheet becomes too thick, and the weldability is reduced. Therefore, from the viewpoint of weldability, it is preferred that the above-mentioned coiling temperature be 800°C or less.
[0176] When a cold-rolled steel sheet is used as the base steel sheet, the hot-rolled steel sheet may be pickled and then cold-rolled according to a conventional method. The reduction ratio in the cold rolling is not particularly limited, but from the viewpoint of the mechanical properties of the steel sheet, the reduction ratio is preferably 30% or more. In addition, from the viewpoint of rolling cost, the reduction ratio is preferably 90% or less.
[0177] The steel sheet may be subjected to recrystallization annealing before hot dip galvanizing. The conditions for the recrystallization annealing are not particularly limited and may be performed in accordance with conventional methods. For example, after the steel sheet is subjected to cleaning treatments such as degreasing, an annealing furnace may be used to heat the steel sheet to a predetermined temperature in the heating zone of the front section, and a predetermined heat treatment may be performed in the soaking zone of the rear section. The atmosphere in the annealing furnace is not particularly limited, but a reducing atmosphere is preferably used to activate the surface layer of the steel sheet.
[0178] (B-2) Recrystallization annealing to increase the dew point
[0179] When the above-mentioned recrystallization annealing is performed, by increasing the dew point of the atmosphere during the recrystallization annealing, internal oxides can be formed inside the surface layer of the steel sheet, and the diffusion rate of Si to the outermost layer of the steel sheet during the hot dip coating process can be reduced. In order to obtain the above-mentioned effect, the dew point needs to be above 0°C. There is no particular upper limit to the above-mentioned dew point, but in order to stably control the dew point at above 20°C, a large humidification device is required, resulting in high equipment costs. Therefore, the above-mentioned dew point is preferably below 20°C.
[0180] (B-3) Formation of Fe-based pre-plating layer
[0181] It is preferred to form an Fe-based pre-plating layer on the above-mentioned base steel plate before hot-dip plating. By forming an Fe-based pre-plating layer on the surface of the base steel plate, the amount of Si in the outermost layer of the steel plate can be reduced, and as a result, the cross-sectional area ratio of the Si-rich phase in the hot-pressed steel plate can be reduced. The composition of the above-mentioned Fe-based pre-plating layer is not particularly limited, but from the above-mentioned viewpoint, the Si concentration in the above-mentioned Fe-based pre-plating layer is preferably less than 0.1%, and it is more preferred that the above-mentioned Fe-based pre-plating layer does not substantially contain Si. The total concentration of components other than Fe contained in the above-mentioned Fe-based pre-plating layer is preferably less than 10%. In other words, the above-mentioned Fe-based pre-plating layer is preferably a plating layer containing more than 90% Fe. The above-mentioned Fe-based pre-plating layer can be, for example, a Fe-plated layer, a Fe-P alloy-plated layer, a Fe-B alloy-plated layer, or a Fe-O alloy-plated layer.
[0182] The Fe-based pre-plating layer is not particularly limited in its film-forming method, but is preferably formed by electroplating, which is excellent in film-forming speed and economic efficiency. From the perspective of stabilizing the plating quality, the Fe-based pre-plating layer preferably has an adhesion amount of 100 mg / m 2 On the other hand, even if the adhesion amount is increased excessively, the effect of reducing the amount of Si in the outermost layer of the steel sheet will be saturated, and the manufacturing cost will only increase. Therefore, the adhesion amount of the above-mentioned Fe-based pre-plating layer is preferably 10 g / m 2 the following.
[0183] [Hot dip galvanizing]
[0184] In the present invention, the steel sheet is immersed in a hot dip coating bath to form a coating layer. As the coating bath, a coating bath having the following component composition needs to be used. The reason for this is described below.
[0185] The composition contains Si: 0.5-7.0%, and
[0186] Fe: 0-10.0%,
[0187] The remainder consists of Al and inevitable impurities.
[0188] Si: 0.5-7.0%
[0189] Si is an element that reacts with Al in the bath, Fe, Mn, etc. of the base material to form an interface alloy layer in the hot-pressed steel sheet. If the Si content in the plating bath is less than 0.5%, the growth of the interface alloy layer in the plating bath is significantly accelerated, forming a film with poor cold workability, and it is difficult to stably obtain a plating layer with a thickness of 10 to 30 μm. Therefore, the Si content is 0.5% or more. On the other hand, if the Si content is higher than 7.0%, the cross-sectional area ratio of the Si-rich phase in the hot-pressed steel sheet is higher than 30%. Therefore, the Si content is 7.0% or less.
[0190] In order to obtain a hot-pressed steel sheet having a cross-sectional area ratio of a Si-rich phase of 30% or less, in addition to reducing the Si content in the coating bath to 7.0% or less as described above, at least one of (B-1), (B-2) and (B-3) above needs to be performed.
[0191] Fe: 0-10.0%
[0192] Fe is a component that is dissolved from the steel sheet or the equipment in the bath and exists in the bath. If the Fe content in the plating bath exceeds 10.0%, the amount of scum in the bath is too large and adheres to the plated steel sheet, resulting in deterioration of the appearance quality. Therefore, the Fe concentration in the plating bath is 10.0% or less, preferably 5.0% or less, and more preferably 3.0% or less. From the viewpoint of appearance quality, the lower the Fe concentration in the plating bath, the better. Therefore, the lower limit of the Fe content in the plating bath is 0%. It should be noted that even if the Fe content in the plating bath is 0%, an intermetallic compound layer is formed by the reaction of the base iron with the components of the plating bath during hot dip plating.
[0193] The component composition of the above-mentioned plating bath may further contain Mg.
[0194] Mg: 0.1~4.0%
[0195] In order to further reduce the amount of hydrogen intruding during the hot pressing process, as described above, Mg may be added to the metal layer of the hot pressing steel sheet, and an appropriate amount of Mg may be added to the plating bath for this purpose. The Mg concentration in the metal layer is of the same value as that in the plating bath, so the preferred range of the Mg content in the plating bath and the reasons therefor are the same as those described for the Mg concentration in the metal layer.
[0196] Examples of the unavoidable impurities include components derived from the base steel plate and unavoidable impurities contained in the metal material (ingot, etc.) for supplying hot dip coating bath components. The total content of the unavoidable impurities is not particularly limited, but is preferably 1% or less in total.
[0197] In other embodiments of the present invention, the composition of the hot dip coating bath may further contain at least one selected from Mn, V, Cr, Mo, Ti, Ni, Co, Sb, Zr and B in a total amount of less than 1%.
[0198] The temperature of the above-mentioned plating bath is preferably in the range of solidification start temperature + 20°C to 700°C. If the temperature of the plating bath is (solidification start temperature + 20°C) or higher, local solidification of components caused by local temperature drop of the plating bath can be prevented. In addition, if the temperature of the plating bath is 700°C or lower, rapid cooling after plating is easy, and the intermetallic compound layer formed between the steel plate and the metal layer can be prevented from becoming too thick.
[0199] The temperature of the base steel sheet immersed in the above-mentioned coating bath (immersion sheet temperature) is not particularly limited, but is preferably controlled within ±20°C of the temperature of the above-mentioned coating bath from the viewpoint of ensuring coating characteristics in the continuous hot-dip coating operation and preventing changes in the bath temperature.
[0200] The immersion time of the steel sheet in the hot dip coating bath is not particularly limited, but is preferably 1 second or longer from the viewpoint of stably ensuring the coating thickness. On the other hand, the upper limit of the immersion time is not particularly limited, but is preferably 5 seconds or shorter from the viewpoint of preventing the intermetallic compound layer formed between the steel sheet and the metal layer from becoming too thick.
[0201] It should be noted that the immersion conditions of the above-mentioned base steel plate in the above-mentioned plating bath are not particularly limited. For example, when a relatively thin steel plate with a plate thickness of 0.6 mm or more and less than 1.6 mm is plated, a line speed of about 150 to 230 mpm is preferred. When a relatively thick steel plate with a plate thickness of 1.6 mm to 3.0 mm is plated, a line speed of about 40 mpm is preferred. In addition, the immersion length is preferably about 5 to 7 m.
[0202] In the present invention, the method for cooling the base steel plate after immersion in the coating bath is not particularly limited and can be performed by any method. The cooling is preferably performed in a nitrogen atmosphere. The reason why the cooling is preferably performed in a nitrogen atmosphere is that there is no need to extremely increase the cooling rate and no need for large-scale cooling equipment, so it is economically excellent. The nitrogen atmosphere may contain 4% by volume or less of hydrogen.
[0203] Without particular limitation, the production of the hot press steel sheet is preferably carried out in a continuous hot dip coating equipment. It should be noted that as the continuous coating equipment, any one of a continuous coating equipment with a non-oxidizing furnace and a continuous coating equipment without a non-oxidizing furnace can be used. The hot press steel sheet of the present invention does not require such special equipment and can be implemented by a general hot dip coating equipment, so it is excellent in productivity.
[0204] Example
[0205] Hereinafter, the function and effect of the present invention will be described using examples. However, the present invention is not limited to the following examples.
[0206] First, the base steel plate is prepared according to the following steps.
[0207] Steel having a composition containing, by mass%, C: 0.34%, Si: 0.25%, Mn: 1.20%, P: 0.005%, S: 0.001%, Al: 0.03%, N: 0.004%, Ti: 0.02%, B: 0.002%, Cr: 0.18%, and Sb: 0.008%, with the remainder being Fe and inevitable impurities, was melted in a converter and cooled in the atmosphere to obtain a steel billet. The Ac3 transformation point of the steel was 783°C and the Ar3 transformation point was 706°C.
[0208] The steel slab was heated to 1200° C. and then hot rolled to produce a hot rolled steel sheet with a thickness of 3.0 mm. The final rolling temperature of the hot rolling was 930° C. The obtained hot rolled steel sheet was coiled at the coiling temperature shown in Table 1 and then cooled in the atmosphere.
[0209] The hot-rolled steel sheet was pickled and then cold-rolled to obtain a cold-rolled steel sheet having a thickness of 1.4 mm.
[0210] An Fe-plated layer is formed as a pre-plated layer on the surface of the obtained cold-rolled steel sheet. The Fe-plated layer is formed by electroplating under the following conditions. It should be noted that for comparison, the Fe-plated layer is not formed in some examples (Table 1).
[0211] Plating solution composition
[0212] Ferrous sulfate: 300g / L
[0213] Sodium sulfate: 50g / L
[0214] pH: 1.8~2.2
[0215] ·Liquid temperature: 55℃
[0216] Current density: 100A / dm 2
[0217] ·Fe coating adhesion: 500mg / m 2
[0218] The base steel sheet was immersed in a plating bath having the composition shown in Table 1 for hot dip plating. The bath temperature of the plating bath used was 660°C. After the steel sheet was pulled out from the plating bath, it was cooled at an average cooling rate of 15°C / sec to solidify the plating layer, thereby obtaining a steel sheet for hot pressing. The cooling was performed by wiping with N2 gas.
[0219] The thickness of the plated layer, the component composition of the metal layer, and the cross-sectional area ratio of the Si-rich layer were measured for the obtained hot-pressing steel sheet by the following method.
[0220] (Thickness of coating)
[0221] Each of the hot-pressed steel sheets was buried in a conductive resin, and a cross section was observed by SEM to obtain a backscattered electron image. The above observation was performed in 5 randomly selected fields of view at a magnification of 500 times. The obtained backscattered electron image was image analyzed according to the contrast, and the area of the coating in the field of view was calculated and divided by the width of the field of view to obtain the average thickness of the coating in the field of view. The arithmetic mean of the average thickness of the 5 fields of view was used as the thickness of the coating in the hot-pressed steel sheet.
[0222] (Cross-sectional area ratio of Si-rich phase)
[0223] The element distribution and concentration of the interface alloy layer of each hot-pressed steel plate were quantified using an electron beam probe microanalyzer (EPMA). The above observation was carried out in 5 randomly selected fields of view at a magnification of 1000 times. First, a threshold value of the contrast of the backscattered electron image was set, and the interface alloy layer between the metal layer and the base material was extracted to obtain the cross-sectional area (S1) of the interface alloy layer. It should be noted that the hot-pressed steel plates of all embodiments have an interface alloy layer and a metal layer on the interface alloy layer.
[0224] Next, based on the quantitative value obtained by EPMA, the region with a Si concentration of 4 mass % or more was defined as a Si-rich phase, and the cross-sectional area (S2) of the Si-rich phase was determined. For each of the five fields of view, the cross-sectional area ratio of the Si-rich phase to the entire interface alloy layer was determined by dividing the obtained S2 by S1, and the average value was used as the cross-sectional area ratio of the Si-rich layer in the hot-pressing steel sheet.
[0225] (Metal layer composition)
[0226] The metal layer of each hot-pressed steel sheet was measured for element distribution and concentration using EPMA in the same manner as the interface alloy layer. The above measurement was performed in 5 randomly selected fields of view at a magnification of 1000 times. First, the metal layer was extracted by setting a threshold value of the contrast of the backscattered electron image, and the surface analysis was performed using EPMA in the above metal layer to measure the average composition of the metal layer. The measured values in the 5 fields of view were averaged as a representative value.
[0227] Next, the obtained hot-pressed steel sheet was hot-pressed according to the following steps to produce a hot-pressed component. First, a 100 mm × 200 mm test piece was taken from the hot-pressed steel sheet and heated in an electric furnace. The heating temperature in the heat treatment was 910°C, the heating time was 210 seconds, and the holding time was 180 seconds. The heating was performed in an atmosphere with a dew point of 10°C.
[0228] After the prescribed holding time, the test piece was taken out of the electric furnace and immediately hot-pressed at a molding start temperature of 720°C using a hat-shaped mold to obtain a hot-pressed part. It should be noted that the shape of the obtained hot-pressed part is a flat portion length of 100 mm on the upper surface, a flat portion length of 30 mm on the side, and a flat portion length of 20 mm on the lower surface. In addition, the curvature R of the mold is 7R on both shoulders of the upper surface and both shoulders of the lower surface.
[0229] The thickness and composition analysis of the Al—Fe based intermetallic compound layer and the morphology of the Fe-rich phase were measured for the obtained hot pressed component by the following method. The measurement results are shown in Table 3.
[0230] (Thickness of Al-Fe intermetallic compound layer)
[0231] The flat part on the top of the obtained hot-pressed component is buried in a conductive resin, and the cross section is observed by SEM to obtain a backscattered electron image. The above observation is carried out in 5 randomly selected fields of view at a magnification of 500 times. The obtained backscattered electron image is analyzed according to the contrast, and the area of the Al-Fe intermetallic compound layer in the field of view is calculated, and the average thickness of the Al-Fe intermetallic compound layer in the field of view is divided by the width of the field of view. The arithmetic mean of the average thickness of the 5 fields of view is taken as the representative value of the thickness of the Al-Fe intermetallic compound layer in the hot-pressed component.
[0232] (Analysis of the morphology of the Al-Fe based intermetallic compound layer)
[0233] The flat part on the top of the obtained hot-pressed part is buried in a conductive resin, and the element distribution and concentration are quantified by EPMA in a field of view including the entire thickness of the Al-Fe alloy layer. The above observation is carried out in 5 randomly selected fields of view at a magnification of 1000 times. According to the quantitative value using EPMA, the area with an Al concentration of less than 40% by mass is set as the Fe-rich phase, and the remaining part, that is, the area with an Al concentration of more than 40% by mass is set as the Al-rich phase. The cross-sectional area ratio of the Fe-rich phase is calculated by dividing the area of the Fe-rich phase in each field of view by the area of the Al-Fe-based intermetallic compound layer, and the average value of the above cross-sectional area ratio in the 5 fields of view is used as the cross-sectional area ratio of the Fe-rich phase in the hot-pressed steel plate. In addition, the length of the cross-sectional direction of the independent Fe-rich phase in the plate surface direction in each field of view is measured and the measured values of all 5 fields of view are averaged to obtain the average length of the cross section of the Fe-rich phase in the direction perpendicular to the plate thickness direction.
[0234] In order to evaluate the resistance of the obtained hot pressed parts to hydrogen embrittlement caused by hydrogen intruding during hot pressing, the amount of diffusible hydrogen in the steel was measured immediately after pressing, and the change in the amount of hydrogen over time during storage at room temperature was measured to measure the desorption rate of hydrogen.
[0235] (Diffusible hydrogen content in steel)
[0236] The amount of diffusible hydrogen of the hot-pressed component just after pressing is determined by the following method. A small piece of 10×15 mm is cut out from the flat part with a small degree of processing of the hot-pressed component, and ground with a precision router to remove the intermetallic compound layer and the diffusion layer on both sides. Then, a temperature desorption analysis is performed, and the cumulative value of the amount of hydrogen when the temperature is raised to 300 degrees is set as the diffusible hydrogen amount. In the above-mentioned temperature desorption analysis, a temperature desorption analysis device manufactured by J·Science is used, the carrier gas is argon, and the heating rate is 200℃ / s. The amount of diffusible hydrogen in the obtained steel is evaluated according to the following criteria. The evaluation results are shown in Table 3.
[0237] 1: Less than 0.30 mass ppm
[0238] 2: 0.30 mass ppm or more and less than 0.50 mass ppm
[0239] 3: 0.50 mass ppm or more and less than 1.00 mass ppm
[0240] 4: 1.00 mass ppm or more
[0241] (Hydrogen desorption time)
[0242] For hot-pressed parts that are stored in a constant temperature room at 25 degrees for 24 hours or 1 week after hot pressing, small pieces are cut out and the amount of diffusible hydrogen in the steel is measured in the same manner as the measurement of the amount of diffusible hydrogen just after pressing. For the time change of the amount of diffusible hydrogen, an approximate formula using an exponential function is prepared using the least squares method based on the data of the three points just after hot pressing, 24 hours later, and 1 week later. According to the above approximate formula, the time required for the amount of diffusible hydrogen in the steel to drop to 0.20 mass ppm is inferred, and it is taken as the hydrogen desorption time. It should be noted that for hot-pressed parts with a diffusible hydrogen amount of less than 0.20 mass ppm just after heat treatment, the evaluation of hydrogen desorption is not performed. Based on the obtained hydrogen desorption time, the hydrogen desorption characteristics are evaluated according to the following criteria. The evaluation results are shown in Table 3.
[0243] 1: Less than 24 hours
[0244] 2: More than 24 hours and less than 120 hours
[0245] 3: More than 120 hours and less than 240 hours
[0246] 4: More than 240 hours
[0247] -: The amount of diffusible hydrogen immediately after heat treatment was less than 0.20 mass ppm, so no evaluation was performed
[0248] Based on the evaluation results of the amount of diffusible hydrogen in the steel and the hydrogen desorption time, a comprehensive evaluation was performed according to the following criteria.
[0249] 1: The amount of diffusible hydrogen in steel is 1
[0250] 2: The amount of diffusible hydrogen in the steel is 2 or 3 and the hydrogen desorption time is 1 or 2
[0251] 3: The amount of diffusible hydrogen in the steel is 2 or 3 and the hydrogen desorption time is 3
[0252] 4: At least one of the amount of diffusible hydrogen in the steel and the hydrogen desorption time is 4
[0253] As shown in the results in Table 3, the comprehensive evaluation of the hot-pressed parts that meet the conditions of the present invention is 2 or 1. That is, the amount of diffusible hydrogen in the hot-pressed parts of the present invention is as low as 0.30 mass ppm or less immediately after hot pressing, and the risk of hydrogen embrittlement is small, or even if the amount of hydrogen immediately after hot pressing is as high as more than 0.30 mass ppm, it can be easily reduced to 0.20 mass ppm or less by storing at room temperature for less than 120 hours, and the risk of embrittlement caused by hydrogen intruding during manufacturing can be easily reduced. On the other hand, the amount of hydrogen in the hot-pressed parts that do not meet the conditions of the present invention is large immediately after hot pressing, and it is also difficult to reduce the amount of hydrogen in a short time.
[0254] [Table 1]
[0255] Table 1
[0256] [Table 2]
[0257] Table 2
[0258]
[0259] [Table 3]
[0260] Table 3
[0261]
Claims
1. A hot pressing component, comprising: Steel, an Al-Fe-based intermetallic compound layer having a thickness of 10 to 35 μm and disposed on at least one surface of the steel material; and a diffusion layer disposed at an interface between the Al-Fe based intermetallic compound layer and the steel material; The Al-Fe-based intermetallic compound layer includes an Al-rich phase having an Al concentration of 40 mass % or more and an Fe-rich phase having an Al concentration of less than 40 mass %, The average length of the cross section of the Fe-rich phase in a direction perpendicular to the plate thickness direction is 10 μm or less.
2. The hot pressing component according to claim 1, wherein: The amount of diffusible hydrogen in the steel material is 0.30 mass ppm or less.
3. A hot pressing steel plate, comprising: Base steel plate, and a plating layer with a thickness of 10 to 35 μm disposed on at least one surface of the base steel plate; The coating has: an interface alloy layer disposed on the parent steel plate, and A metal layer having an Al content of 50 mass % or more disposed on the interface alloy layer; The interface alloy layer comprises a Si-rich phase having a Si concentration of 4 mass % or more, The cross-sectional area ratio of the Si-rich phase to the entire interface alloy layer is 5% to 30%.
4. The hot pressing steel sheet according to claim 3, wherein: The metal layer contains Si: 0.5 to 7.0 mass % and Fe: 0 to 30 mass %.
5. The hot pressing steel sheet according to claim 4, wherein: The metal layer further contains Mg: 0.1 to 4.0 mass %. 6 . A method for producing a hot pressed component, comprising hot pressing the steel sheet for hot pressing according to claim 3 to produce a hot pressed component.
Citation Information
Patent Citations
Aluminum-base plated steel sheet for hot press superior in corrosion resistance and heat resistance, and member for automobile using it
JP2003034845A